Urban Planning and Reconstruction of Cities Post-Wars by the Approach of Events and Response Images - Suhad K. Al-Mosawy; Ahmed A. Al-Jaberi; Tuqa R. Alrobaee; Ahmed S. Al-Khafaji (Civil Engineering Journal, 2021)
The research attempts to shed light on how to invest the philosophical and intellectual concept of the event in preparing the development plans for the city. Based on it, there are three strategies to read the event (Explanation, Interpretation, and Deconstruction) that are regularly responded to it with three strategies represented by (Revitilaization, Renewal, and Reform). Through the use of reading and response strategies, and the corresponding planning policies represented by: preservation, rehabilitation, and redevelopment. The research adopted an analytical and descriptive methodology for some world experiences for the eventful cities, such as Warsaw, which reflects (Explanation - Revitilaization) and used preservation, Bilbao, which reflects (Interpretation - Renewal) and used rehabilitation, and Tianjin, which reflects (Deconstruction - Reform) and used redevelopment. In an attempt to benefit from these experiences and derive some indicators for each strategy. By applying the derived indicators to the traditional Mosul city, it concluded that the most appropriate strategy for the reconstruction of this city is the strategy of Explanation – Revitalization, which represents preservation because the destruction of the city was intending to crush the historical and cultural value of the city and destroy the local and national identity. Doi: 10.28991/cej-2021-03091763 Full Text: PDF